Peraturan Kesehatan Internasional dan Strategi Ekonomi : Komitmen Indonesia dalam International Health Regulations (IHR) - Sherly Tricia Ningsih (Universitas Diponegoro, 2025)
In May 2005, the 58th World Health Assembly adopted the International Health Regulations (IHR) to enhance global responses to public health threats by strengthening state capacities while minimizing disruptions to international travel and trade. Member states are required to report their ability to detect, assess, and respond to global health threats and allocate sufficient budgets to support national health systems. Indonesia committed to implementing the IHR in June 2007, targeting full implementation by 2014 despite challenges in its domestic health sector. This study explores Indonesia’s commitment to implementing the IHR (2005) using Robert O. Keohane’s neoliberal institutionalism approach, which emphasizes the role of international institutions in shaping state behavior through cooperative rules to achieve mutual benefits. Employing a qualitative approach and literature review, it analyzes secondary data from government documents, international reports, and prior research. The findings indicate that Indonesia’s commitment was driven by humanitarian, political, and economic considerations, aiming to balance domestic and international health policies while strengthening its health system to address global challenges.